Analisis Yuridis Putusan Perkara Tindak Pidana Penganiayaan yang Dilakukan terhadap Anak (Pusat Riset dan Inovasi Nasional, 2026)
Criminal acts of assault against children constitute a serious violation of human rights that requires optimal legal protection by the state. As legal subjects, children are entitled to security, protection from violence, and guarantees for proper growth and development, as mandated by Pancasila, the 1945 Constitution of the Republic of Indonesia, and relevant child protection legislation. This study aims to conduct a juridical analysis of the legal considerations applied by judges in Decision Number 83/Pid.Sus/2020/PN.Kot concerning the criminal offense of assault committed against a child, as well as to assess their conformity with criminal law principles, child protection law, and the objectives of sentencing. This research employs a normative legal research method using statutory, conceptual, and case approaches, supported by primary, secondary, and tertiary legal materials. The findings reveal that although the legal basis applied refers to Law Number 35 of 2014 on Child Protection, the judicial considerations have not been comprehensively formulated, as they insufficiently incorporate sociological, criminological, and child-centered protection perspectives. Consequently, the sentence imposed is relatively lenient and fails to fully reflect the objectives of punishment, particularly deterrence and sustainable protection for child victims. Therefore, strengthening the quality of judicial reasoning and ensuring the optimal application of relevant legal provisions are essential to achieve legal certainty, justice, and effective protection for children as victims of violent crimes.